Dynamics of the Development of Dialectical and Logical Thinking in the Senior Preschool and Primary School Age - N.E. Veraksa; Z.V. Airapetyan; O.V. Almazova; K.S. Tarasova (Психолого-педагогические исследования, 2023)
Earlier in our research we studied the differences between formal and dialectical thinking, so formal operations are aimed at the exclusion of contradiction, and dialectical ones at the active transformation of the relations of opposites. The clarification of the relationship between these two forms of thinking in dynamics continues to be a relevant task. The aim of the work was to investigate the performance in solving logical and dialectical tasks, as well as to identify age norms for 5-10-year-old children (n=756). To assess logical thinking, we used J. Piaget's tests, which are aimed at assessing the ability to coordinate two parameters simultaneously when analyzing proportions ("Probability"), balance ("Scales") and motion ("Mechanical curve"). Methods aimed at assessing children's ability to perform dialectical thought actions of transformation ("Drawing of an unusual tree"), mediation ("What can be both at the same time?"), and seriation ("Cycles") were applied. By 8-10 years of age, the majority of children successfully coped with the solution of all three logical tests, with boys performing better than girls on a spatial task aimed at coordinating multidirectional movements ("Mechanical curve"). Most children by the age of 9 successfully cope with building cyclical seriations. At the same time, dialectical tasks, as a result of which one object transforms into its opposite ("Drawing of an unusual tree") or both objects are combined into a single new one ("What can be both at the same time?") are relevant for children over 10 years old. It is probable that, as thinking is formed at each age stage, the ability to identify and operate with opposites retains its significance.